Ultra-high speed imaging study of the diesel spray close to the injector tip at the initial opening stage with split injection. (1st February 2016) - Wang, Ziman; Ding, Haichun; Ma, Xiao; Xu, Hongming; Wyszynski, Miroslaw L.
Highlights: Ultra-high speed micro imaging was used to study diesel spray. Primary breakup of diesel spray from split injections were investigated. Factors affecting the primary breakup characteristics were studied. Combined effects of the factors on primary breakup were analyzed. Abstract: This study focused on the primary breakup of diesel spray at the initial injector opening stage with split injection strategy at injection to atmospheric conditions. An ultrahigh speed CCD camera was employed to investigate the primary breakup of spray by photography technique with the help of backlighting. The injection pressure, dwell duration, distribution of injection duration between split injections and the number of the splits significantly affected the strength of primary collision and thus the primary breakup characteristics. Besides, the spray characteristics of the split injections except those of the first split injection were simultaneously affected by three main factors, namely, induced air driving force, lower mass flow rate and primary collision. The combined influence of the injection pressure, injection duration distribution and dwell duration determined the main effect on the affected split injections.